2023
DOI: 10.1002/inmd.20230009
|View full text |Cite
|
Sign up to set email alerts
|

Salivary analysis: An emerging paradigm for non‐invasive healthcare diagnosis and monitoring

Abstract: As an emerging non-invasive and easy-to-use toolkit, salivary analysis has garnered significant attention recently. By leveraging the latest discoveries in salivary biomarkers, salivary analysis has the potential to revolutionize the field of healthcare by providing valuable information for monitoring an individual's health status, diagnosing disease progression, and enabling personalized treatment. However, the transitional development of breakthrough salivary analysis remains an intriguing challenge. Only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Storage stability refers to the ability of the sensor to retain its performance and functionality over time when stored under specific conditions. 51,52 In our case, certain sensor materials may exhibit degradation or chemical reactions that can lead to changes in their sensing performance, resulting in unreliable or inaccurate measurements. Our results showed that the prepared colorimetric sensors, including the chlorine sensor and glucose sensor, could only sustain 1 day when kept in the lab environment (∼25 °C, humidity level: ∼50%) and maintained sufficient sensing capability for 3 days when stored in a refrigerator (∼4–8 °C, humidity level: ∼40–50%).…”
Section: Resultsmentioning
confidence: 99%
“…Storage stability refers to the ability of the sensor to retain its performance and functionality over time when stored under specific conditions. 51,52 In our case, certain sensor materials may exhibit degradation or chemical reactions that can lead to changes in their sensing performance, resulting in unreliable or inaccurate measurements. Our results showed that the prepared colorimetric sensors, including the chlorine sensor and glucose sensor, could only sustain 1 day when kept in the lab environment (∼25 °C, humidity level: ∼50%) and maintained sufficient sensing capability for 3 days when stored in a refrigerator (∼4–8 °C, humidity level: ∼40–50%).…”
Section: Resultsmentioning
confidence: 99%
“…Early detection of disease is key to decreasing morbidity, and mortality and preventing the complications of disease 21,22 . The role of saliva has been extensively reported not only because of its ease of availability and non-invasive nature of procedure but also due to the abundance of *p-value < 0.05 is considered significant, the Kruskal Wallis, Kendall Tau's Correlation test and, Binary logistic regression were applied genetic material and proteins in saliva samples 23,24 .…”
Section: Resultsmentioning
confidence: 99%
“…We worked with saliva samples to provide microbial information about the oral cavity. The analysis of the salivary microbiome has gained attention as a non-invasive method for assessing oral and systemic health [ 27 ]. Changes in the salivary microbiome have been linked to periodontal disease, dental caries, and systemic diseases like diabetes and cardiovascular disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%